GENERAL PHYSICAL FITNESS OF YOUNG ITF TAEKWONDO ATHLETES (Physical Culture and Sport: Scientific Perspective, 2024)
Improvement of physical fitness of taekwondo athletes should be carried out in certain areas, determination of which is possible via methodological approaches, namely data search in academic references, specialists polling, the study of the level of athletes fitness at various age segments. The aim of the research is to determine overall physical fitness and its differences between young taekwondo athletes of various age groups. Methods of research are as follows: theoretical analysis and generalization; pedagogical testing; methods of mathematical statistics. The following tests were used: shuttle running 3x10 m, 30-meter dash; 1000-meter sprint; pull-ups; body lifting in sitting position; medicine ball toss from the floor upfront; length leap from the spot; jump-rope for 60 s; squats on one leg for 30 s; multiple jumps for 20 s; cross splits; upfront body tilt; “bridge” in lying position; 8-shape running with direction changes; three forward circles, three back circles; Romberg test with eyes closed; walk deviations at 5-meter section. 45 athletes of the following age groups took part in the research: 7–9, 10–11, 12–14, and 15–17. Results. In the process of aging, young taekwondo athletes show gradual improvement of strength and speed and strength qualities. In the age of 10-14 taekwondo athletes have the least number of statistically probably differences in the indices of general physical fitness, which can prove the need for search of optimal orientation of the content of physical training. Athletes aged 15-17 showed better coordination abilities, while athletes aged 7-9 showed better flexibility compared to other age groups of taekwondo athletes. In the number of tests, we have not indentified any, or indentified at least one statistically probably difference between average group results of taekwondo athletes of various age groups. These tests included the following: squats on one leg for 30 s and multiple jumps for 20 s by the number of jumps made; forward body tilting and walk deviations at 5-meter section. Conclusions. We may state that not all manifestations of physical qualities are peculiar to the improvement of the results in various age groups of young taekwondo athletes. This is more specific to the results at tests on manifestation of speed, strength, speed and strength qualities, and less specific to manifestations of coordination abilities and flexibility.
Keywords: level; differences; general physical fitness; young athletes; age groups; ITF taekwondo